2003
DOI: 10.1016/s0014-5793(03)00213-8
|View full text |Cite
|
Sign up to set email alerts
|

ArhGAP15, a novel human RacGAP protein with GTPase binding property1

Abstract: We have previously described a partial cDNA sequence encoding a RhoGAP protein, GAP25 that is homologous to the recently reported ArhGAP9 and ArhGAP12. We now describe a related new member ArhGAP15 that shares a number of domain similarities, including a pleckstrin homology (PH) domain, a RhoGAP domain and a novel motif N-terminal to the GAP domain. This novel motif was found to be responsible for nucleotide-independent Rac1 binding. Using swop mutants of Rac/Cdc42, we have established that the binding is thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 21 publications
2
62
0
Order By: Relevance
“…ARHGAP15 is a RAC binding protein, and the mutation is at the proximal end of the RAC binding domain (PS50238) of the protein (10), suggesting a possible mechanism for any effect of the mutation on function. RAC1 is a GTPase that is active when binding GTP and inactive when binding GDP; the RhoGAP domain of ARHGAP15 accelerates the intrinsic rate of hydrolysis of GTP to GDP, thereby inactivating RAC1 (10). To determine whether the ARHGAP15 282H→P polymorphism might cause a difference in the rate of GTP hydrolysis by RAC1, the two alleles were expressed in vitro, and the rate of GTP hydrolysis was measured by following the change in absorbance at 360 nm caused by an increase in γP i abundance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ARHGAP15 is a RAC binding protein, and the mutation is at the proximal end of the RAC binding domain (PS50238) of the protein (10), suggesting a possible mechanism for any effect of the mutation on function. RAC1 is a GTPase that is active when binding GTP and inactive when binding GDP; the RhoGAP domain of ARHGAP15 accelerates the intrinsic rate of hydrolysis of GTP to GDP, thereby inactivating RAC1 (10). To determine whether the ARHGAP15 282H→P polymorphism might cause a difference in the rate of GTP hydrolysis by RAC1, the two alleles were expressed in vitro, and the rate of GTP hydrolysis was measured by following the change in absorbance at 360 nm caused by an increase in γP i abundance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with a role of PIP3 in controlling the duration rather than the triggering of Rac activity (7) and suggest an involvement of PI3K in mediating GAP activation in response to chemoattractants. PI3K signaling is a known activator of GAPs (38) and PIP3 might modulate those RacGAPs that, like ArhGAP15, are switched on by PH-domainmediated plasma membrane recruitment (24). However, RacGAP were found modulated even after cell lysis, thus suggesting that membrane translocation is accompanied by other events, possibly involving more stable modifications like, for example, RacGAP phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…To find a potential PI3K␥-regulated RacGAP, bioinformatic analysis of coexpression data was performed (23). This approach led to the identification of ArhGAP15, a leukocyte-expressed PH-domain containing GTPase-activating protein (GAP) for Rac, triggered by plasma membrane translocation (24). The expression of a myctagged ArhGAP15 by lentiviral transduction in wild-type BMDMs (expression analysis not shown) revealed that this protein, although increasing cell rounding and blocking polarization, was in the cytoplasm in resting conditions but localized to plasma membrane after C5a stimulation (Fig.…”
Section: Constitutive and Delocalized Pip3 Production Impairs Leadingmentioning
confidence: 99%
“…ArhGAP15, a protein known to possess Rac-GAP activity (25), also appeared among the proteins that became phosphorylated only in the presence of Pak2 and [␥-32 P]ATP (Fig. 1A).…”
Section: Pak2 Phosphorylates Arhgap15 At One or More Serine Residues-mentioning
confidence: 99%